Integration of Islamic Values in Independent Curriculum: Challenges and Opportunities in the Digital Era - Yayan Mailiyana Prihatin; Feni Nur Indayanti; Moh Ali (Lembaga Yasin AlSys, 2025)
The integration of Islamic values into the Independent Curriculum (Kurikulum Merdeka) represents a strategic effort to cultivate students' character development spiritually, intellectually, and socially within the context of an increasingly complex digital era. This study explores the conceptual foundation, urgency, challenges, and opportunities associated with embedding Islamic values as part of character education in the Independent Curriculum. Employing a literature study with a descriptive qualitative approach, the research highlights that the curriculum’s flexible structure enables the contextual incorporation of values such as honesty, tolerance, and responsibility across diverse subjects. The study identifies key challenges, including limited digital literacy among educators and unequal access to technological resources. Nonetheless, the digital era also presents significant opportunities through the utilization of social media and online learning platforms to deliver Islamic values in more innovative and engaging ways. The findings suggest that, with appropriate strategies and supportive educational policies, the Independent Curriculum can serve as an effective and sustainable vehicle for internalizing Islamic values in a manner that remains relevant to contemporary educational needs.